The Effect of Learning Biophysics with STEM Approach on Science Process Skills and Critical Thinking: Field Study on Application of NA-AOGS for Increasing Soybean Productivity and Growth Rate - Rosana, D.; Kadarisman, N.; Purwanto, A.; Sari, E. K. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
Efforts to fulfill food security to anticipate population growth in Indonesia need to be supported by universities through research and community service. The application of the Natural Animal Audio Organic Growth System (NA-AOGS) with a STEM (Science, Technology, Engineering, and Mathematics) approach is an effort to help the community increase crop yields and accelerate the growth of soybeans (Glycine max (L.) Merill). The research method used is R&D (Research & Development) which is modified from Cennamo and Kalk (2018). This model is in the form of a spiral cycle using 5 (five) main activities as follows: (1) defining the product conceptual; (2) designing research products; (3) demonstrating the product in a limited trial; (4) developing the product through the process of evaluating the test results, and (5) presenting the product to the public.Â The direct impact of learning is the improvement of science process skills and critical thinking of students participating in the Biophysics course at the Natural Sciences Study Program, Universitas Negeri Yogyakarta. This is due to the effective application of STEM to link science learning with contextual technology and engineering (NA-AOGS), environmentally friendly technology (only using natural animal sound frequency variables), mathematical elements in data analysis, and analysis of soybeans plant growth charts. The economic impact of this research is the scientific contribution in the form of adaptation of agricultural technology so that it can increase soybean yields (an increase of 130.38% on an area of 2750 m2). The novelty and contribution of this research is the integration of science learning with agricultural techniques and technology with a STEM approach so that it can improve the welfare of farmers in educational institutions as a new model in science learning.